2022
DOI: 10.1080/13621718.2022.2053398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn interlayer on friction stir butt welding of A1100 and SUS316L stainless steel

Abstract: The effect of Zn interlayer on the microstructure and mechanical properties of dissimilar A1100 and SUS316L friction stir welded (FSW) butt joints was investigated. The results showed that Zn could improve the joint's tensile strength. However, a complete dissolution of the Zn interlayer was necessary to achieve a sound joint. During the FSW process, the stirring action of the tool dispersed the Zn into the A1100 matrix forming a solid solution of Zn. A direct relationship was found between the tool rotational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Solid solution strengthening is one of the most dominant hardening mechanisms in wrought Al alloys [22]. The influence of Zn in improving the strength and hardness of Al alloys has been seen clearly in several studies [17, 2225]. The slight variation in the hardness of the A1050 stir zones is due to the differences in the Zn content following the material vortex flow by the FSW tool stirring motion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid solution strengthening is one of the most dominant hardening mechanisms in wrought Al alloys [22]. The influence of Zn in improving the strength and hardness of Al alloys has been seen clearly in several studies [17, 2225]. The slight variation in the hardness of the A1050 stir zones is due to the differences in the Zn content following the material vortex flow by the FSW tool stirring motion.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we summarised the advantages of using a pure 100-μm-thick Zn interlayer on the dissimilar FSW of stainless steel SUS316L and pure Al into two main perspectives: (1) inhibiting the growth of the interfacial Al-Fe IMCs and (2) strengthening the Al stir zone by forming Al-Zn solid solutions [17]. While the first merit was addressed in [17,18], the latter is still of interest to be thoroughly discussed.…”
Section: Introductionmentioning
confidence: 99%
“…low toughness Al 5 Fe 2 ) at the joint interface are the critical metallurgical challenges during dissimilar joining of Al/steel. The presence of brittle intermetallic compounds at the joint interface coupled with the creation of thermal stress induced by a significant thermal expansion mismatch between Al and steels during joining leads to the high susceptibility of Al/steel dissimilar joint to cracking [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state welding processes such as friction stir welding are viable candidates for dissimilar welding of Al and steels [4][5][6][7]. In addition, some metallurgical joining processes, such as resistance spot welding [1,8,9], laser welding [2], arc welding [10], laser/arc hybrid [3], etc., enable Al/steel dissimilar joining via establishing a liquid/solid interface during joining.…”
Section: Introductionmentioning
confidence: 99%
“…The control of IMCs is the most important issue in the FSW process of Al/steel dissimilar joining. Adjusting welding parameters [24][25][26][27][28][29] such as the welding speed, rotating speed, tilt angle, etc., changing the tool design [25], or inserting an interlayer [30] has been widely used to control the IMCs and to optimize the mechanical properties of the Al/steel butt joint. Recently, Zhang et al [31] reported a new FSW butted method with no contact between the tool and the steel plate, in which a thickened Al alloy plate was applied to avoid the tool touching the steel plate.…”
Section: Introductionmentioning
confidence: 99%